Deep Brain Stimulation Increases Seizure Threshold by Altering REM Sleep and Delta Powers During NREM Sleep - Tseng, Hsin-Tzu; Hsiao, Yi-Tse; Yi, Pei-Lu; Chang, Fang-Chia (Frontiers in Neurology, 2020)
We previously demonstrated that seizure occurrences at different zeitgeber times alter sleep and circadian rhythm differently. On the other hand, the synchronized delta wave of electroencephalogram (EEG) during non-rapid eye movement (NREM) sleep facilitates seizure while desynchronized EEG of REM sleep suppresses it. We also elucidated that unilateral deep brain stimulation (DBS) of anterior nucleus of thalamus (ANT) suppresses seizure recurrence. In present study, we intraperitoneally injected pentylenetetrazol (PTZ, 40 mg/kg) for consecutive 14 days (PTZ kindling) to induce spontaneous seizure in rats, and a 30-minute (delivered 10-min before each PTZ injection) or a 3-hour DBS of unilateral ANT (delivered 1–h before each PTZ injection) was applied to suppress seizure. The frequency of DBS stimulation was 200 Hz and the electrical currents consisted of biphasic square pulses with an intensity of 50 μA, an 100 μs pulse width and a 4.1 ms stimulation interval. Our results found that PTZ-induced spontaneous seizure did not cause significantly change the quantity in NREM sleep, but suppressed the amount of REM sleep. Unilateral ANT DBS prolonged the onset latency of ictal seizure, decreased the spontaneous seizure duration, and increased the survival rate, but did not change the amplitudes of epileptiform EEGs during ictal period. Unilateral ANT DBS did not significantly alter NREM sleep, but increased the amounts of REM sleep. Analyzing the spectrograms of Fast Fourier Transforms (FFTs) indicated that intensities of all frequencies were enhanced during the PTZ-induced ictal period and subsequent spontaneous seizure. Thirty minutes of unilateral ANT DBS suppressed the augmentation of low-frequency (< 10 Hz) intensities during the spontaneous seizure induced by PTZ kindling. We further found that consecutive injections of PTZ progressively increased the enhancement of the delta powers during NREM sleep, whereas the unilateral ANT DBS inhibited this progressive enhancement. It was also noticed that 30-min ANT DBS exhibited better efficacy in epilepsy suppression than 3-h ANT DBS. These results elucidated that the unilateral ANT DNS enhanced the seizure threshold by increasing the amounts of REM sleep and decreasing the progressive enhancement of delta power during NREM sleep to suppress spontaneous seizure recurrences in PTZ kindling-induced epileptic rats.